Adolescent Anemia: A Challenge to Global Health: Addressing the Challenge of Adolescent Anemia in Global Health (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Deficit in iron more people than any other condition are affected by anaemia, which is a seriousworldwide health issue and a public health crisis of epidemic proportions. Anemia that has a significantnegative impact on a woman's health and wellbeing raises the chance of unfavourable outcomes for themother and the unborn child. The WHO estimated that anaemia affects 24.8 of the world's population.Children in preschoolers have a prevalence rate of 47.4, whereas men have a prevalence rate of 12.7.However, non-pregnant women, who make up 468.4 million of the population, are the group most severelyimpacted. According to the WHO, Central and West Africa and South Asia have the highest anaemicprevalence rates.Although numerous policies and intervention programmes have significantly decreasedthe prevalence of anaemia, more practical efforts are required to combat the condition and meet the fiftypercent reduction target. The prevalence of anaemia worldwide, its causes, risk factors, and interventiontechniques to treat anaemia have all been covered in this review.